Effectiveness of a Mobile Plant Learning System in a science curriculum in Taiwanese elementary education - Huang, Yueh-Min; Lin, Yen-Ting; Cheng, Shu-Chen (Computers and education, 2010)
This study developed a Mobile Plant Learning System (MPLS) that provides instructors with the ways and means to facilitate student learning in an elementary-school-level botany course. The MPLS represented in this study was implemented to address problems that arise with the use of a didactic approach to teaching and learning botany, as is typically used in elementary schools in Taiwan. To extend opportunities for learning beyond the classroom, this study used personal digital assistants (PDAs) equipped with the MPLS, which provided both teachers and students access to plant information while in the field. A quasi-experimental research design was used to investigate the effectiveness of using the MPLS to support student learning. The responses to questionnaires and interviews indicate that students valued the outdoor learning activities made possible by use of the PDA and its functions. Pre- and post-test results demonstrated that students also benefitted academically from the use of the MPLS and the PDA.